Automated measurement of coagulation and fibrinolytic activation markers: Outcomes in coronavirus disease 2019 (COVID‐19) patients. (22nd April 2022) - Gardiner, Chris; Mackie, Ian J.; MacCallum, Peter; Platton, Sean
Abstract: Background: Severe coronavirus disease 2019 (COVID‐19) is characterized by marked hypoxaemia and lung oedema, often accompanied by disordered blood coagulation and fibrinolytic systems, endothelial damage and intravascular fibrin deposition. Patients/Methods: We present a retrospective observational study of 104 patients admitted to hospital with COVID‐19. Plasma samples were collected within 72 h of admission. In addition to routine coagulation and haematology testing, soluble thrombomodulin (sTM), thrombin‐antithrombin (TAT), tissue plasminogen activator‐plasminogen activator inhibitor 1 complex (tPAI‐C) and plasmin‐α2 antiplasmin complex (PIC) were performed by automated chemiluminescent enzyme immunoassays. Results: Significantly higher levels of D‐dimer, TAT, sTM and tPAI‐C were observed in non‐survivors compared to survivors. To confirm which parameters were independent risk factors for mortality, multiple logistic regression was performed on D‐dimer, TAT. sTM, tPAI‐C and PIC data. Only increasing sTM was significantly associated with mortality, with an odds ratio of 1.065 for each 1.0 TU/mL increment (95% CI 1.025–1.115). Conclusions: Of the haemostatic variables measured, sTM, which can be rapidly assayed, is the best independent predictor of mortality in patients hospitalized with COVID‐19, and this suggests that endothelial dysfunction plays an important role in disease progression.